2009
DOI: 10.1590/s0103-90162009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength, friability and organic carbon in an oxisol under a crop-livestock system

Abstract: The crop-livestock system can promote soil compaction in surface layers, mainly due to animal trampling. However, plants and their root growth, in interaction with animal trampling, can decrease the deleterious changes in soil structure caused by this system. Up to the present time, the physical soil modifications in crop-livestock systems, including oat and ryegrass crops for winter animal forages are unknown. The objective of this study was to quantify and to relate tensile strength, friability and soil orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
(21 reference statements)
2
9
1
6
Order By: Relevance
“…The average TS values obtained in the present study were higher than those reported by Imhoff et al (2002), Giarola et al (2003), Guimarães et al (2009), andFerreira et al (2011). According to Blanco-Canqui et al (2005), TS values are related to soil management and, in sugarcane production systems, the intense tillage prior to the crop establishing, besides the heavy machinery traffic for fertilization, and sugarcane transportation after manual harvesting, may have increased these values, as a result of increased soil density.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…The average TS values obtained in the present study were higher than those reported by Imhoff et al (2002), Giarola et al (2003), Guimarães et al (2009), andFerreira et al (2011). According to Blanco-Canqui et al (2005), TS values are related to soil management and, in sugarcane production systems, the intense tillage prior to the crop establishing, besides the heavy machinery traffic for fertilization, and sugarcane transportation after manual harvesting, may have increased these values, as a result of increased soil density.…”
Section: Resultscontrasting
confidence: 75%
“…Blanco-Canqui et al (2005) also verified an inverse exponential relation between these parameters. However, Guimarães et al (2009) reported a direct between these same parameters in an Oxisol, and attributed this result to a cementing effect of TOC on soil mineral particles with humified SOM. Zhang (1994) reported that there are two opposite relations between SOM and TS: SOM can increase the number and strength of the connections between soil particles; and it can have a dilution effect, which implies the reduction of soil density, or the increase of the porosity of the aggregates.…”
Section: Resultsmentioning
confidence: 95%
“…Guimarães et al (2009) notaram que uma planta de sistema radicular agressivo e crescimento contínuo, aliada à decomposição, pode contribuir para uma diminuição da resistência tênsil no solo. Nesse caso, fica evidente que o SPD bem feito, com elevado aporte de resíduos, associado à rotação de culturas com espécies de diversificado sistema radicular são fatores que reduzem a RT.…”
Section: Resultsunclassified
“…Também em Latossolos da região subtropical, Bartoli et al (1992) e Guimarães et al (2009) reportaram efeito contrário, ou seja, o aumento no conteúdo de C orgânico total (COT) foi proporcional ao maior valor de RT do solo. Segundo esses autores, esse efeito deve-se à cimentação entre as partículas minerais de argila e a matéria orgânica mais humificada do solo.…”
Section: Introductionunclassified
“…Soil structure is a characteristic difficult to measure directly, which is why it is commonly assessed by other properties, such as soil density, porosity (Reynolds et al, 2008), available water (Dexter, 2004), infiltration (Thierfelder and Wall, 2010), soil resistance to penetration and limiting water range (Silva et al, 1994), air permeability (Ball and Schjonning, 2002), tensile strength of aggregates (Guimarães et al, 2009), and the S index (Dexter, 2004).…”
Section: Resumo: Alterações Morfológlcas E Micromorfológicas Na Estrumentioning
confidence: 99%